THE IMPACT OF POSTERS ON STUDENTS' VOCABULARY DEVELOPMENT AT SMA YPPK ST. THOMAS WAMENA - Mabel , Piter; Halitopo, Manase; Yikwa, Pemius (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The objective of this research was to find out if using the poster may improve the students' English vocabulary at SMA YPPK St. Thomas Wamena. With a one-group pre- and post-test, this study used an experimental design. The research instrument utilized the matching method, in which students were required to match pictures with the corresponding vocabulary items. The study was conducted at SMA YPPK St. Thomas Wamena, selecting the seventh-grade students as the population for the 2025/2026 academic year. The researcher applied a cluster sampling technique and selected 30 students as the research sample. Pre- and post-tests were given in order to gather data. Before and after the treatment, students' initial vocabulary mastery was measured with a pre-test, and their performance was evaluated with a post-test. The independent variable in this study was the use of posters, whereas the dependent variable was students’ vocabulary achievement. The findings of the data analysis of the students' vocabulary knowledge in the pre- and post-tests revealed that the t-test value was 17.40 and the t-table value was 2.045. Students' vocabulary competence improved significantly, as evidenced by the t-test value being greater than the t-table value (17.40 > 2.045). This result implies that the pre- and post-test results varied significantly.